Predictive value of gemstone spectral imaging for chemotherapy response in colorectal cancer liver metastases: A retrospective study - Hou-Fa Ning; Yun-Long Qin; Kui-Tao Yue; Shuai Wang; Wei-Guang Shao; Guang-Zhi Wang (Journal of Research in Medical Sciences)
Background: Accurate and timely assessment of tumor response after chemotherapy is crucial in clinical settings. The aim of this study was to explore the feasibility of Gemstone Spectral Imaging (GSI) for early assessment of chemotherapy responses in patients with colorectal cancer liver metastasis (CRCLM). Materials and Methods: From October 2012 to October 2018, 46 patients (28 males and 18 females) with CRCLM received GSI followed by chemotherapy were retrospectively reviewed. The patients were divided into a response group (n = 32) and a nonresponse group (n = 14) according to the tumor response to chemotherapy. The iodine concentration images and virtual monoenergetic images (VMIs) with an optimal contrast-to-noise ratio at the arterial phase (AP) and portal venous phase (PVP) were obtained by GSI viewer. The iodine concentration value and computed tomography (CT) value on VMIs and slope of spectral attenuation curves of all lesions were compared. A logistic regression analysis was used to determine the predictor of chemotherapy response. Results: The difference of extrahepatic metastasis (P = 0.001), CT value on 68 keV VMIs at the AP (P = 0.005) and PVP (P = 0.001), slope of CT value attenuation curves at the AP (P = 0.013) and PVP (P = 0.001), and iodine concentration value at PVP (P = 0.003) between the response and nonresponse groups were statistically significant. The CT value of the 68 keV VMIs (OR: 1.206; 95% confidence interval [CI]: 1.021–1.425, P = 0.027) and the iodine concentration value at PVP (OR: 1.952; 95% CI: 1.034–3.684, P = 0.039) were independent prognostic factors for predicting chemotherapy response. Conclusion: Baseline GSI may help predict the response to chemotherapy and provide a good tumor-response indicator through single-energy CT value of 68 keV at the PVP and iodine concentration.